Novel virtual topology configuration algorithm for IP over WDM network - LE Zi-chun; FU Ming-lei (Tongxin xuebao)
The load balancing for the whole network was chosen as the optimal objective and a novel virtual topology configuration algorithm was proposed.In the proposed algorithm,the load distribution variance was chosen as a key criterion for judging the load balancing.And the definition and the computing method of the load distribution variance were introduced.In addition,the blocking probability was chosen as the main performance parameter for comparing with other algorithms.In the optical layer,the algorithm proposed was compared with the routing with load balancing heuristics（RLBH） algorithm.Similarly,in IP layer,the algorithm was compared with the fixed-path least-congestion（FPLC） algorithm.Moreover,the numerical results of the algorithm comparison were shown and discussed.The simulation results show that the performance of the algorithm is better than RLBH algorithm and FPLC algorithm on the blocking probability.